Medicaid Adapts to Extreme Heat: Evolving State-Based Coverage of Home Air Conditioning - Jenny L. Keroack; Alene Kennedy-Hendricks; Peter J. Winch (SAGE Publishing, 2024)
Anthropogenic climate change is increasing the frequency and severity of extreme heat events, leading to increased morbidity and mortality. Many of the populations at greatest risk from the health threats of extreme heat are also more likely to receive health insurance coverage from the Medicaid program. While Medicaid has not historically covered air conditioners, an increasing number of states are offering coverage. Of the Medicaid programs administered by the 50 states and Washington DC, 13 currently offer an air conditioner coverage benefit and 2 have applied to offer coverage to the federal government. Most of these states have obtained various types of waivers under the Social Security Act to cover air conditioners. Section 1115 waivers tend to offer more flexible and holistic coverage. The states offering coverage vary in the types of air conditioners covered, the approximate frequency with which air conditioners have been furnished, and the billing codes utilized. The lack of a specific billing code or procedure modifier code for air conditioners is a barrier to tracking the effectiveness, reach, and implementation of air conditioner coverage policies within and across states.